PENGGUNAAN MEDIA FLIP CHART DALAM MENINGKATKAN KEMAMPUAN BAHASA VERBAL ANAK AUTIS KELAS II DI SLB NEGERI 1 MAKASSAR - Nurul Safitri Andriani; Dwiyatmi Sulasminah; Bastiana Bastiana (JURNAL ORTO DIDAKTIKA, 2024)
This study examines the improvement of the verbal language skills of autistic children using flip chart learning media in class II autistic children at SLB Negeri 1 Makassar. The formulation of the problem in this study is